Sugar-responsive multifunctional hydrogel as well as preparation method and application thereof in wound dressing

By developing sugar-responsive multifunctional hydrogel in diabetes wound treatment, using the reversible combination and dynamic crosslinking technology of phenylboronic acid monomer and epigallocatecin, the poor efficacy and water treatment of diabetes wound treatment in the prior art are solved. The problem of high gel complexity achieves efficient healing of diabetic wounds and simplifies the production process.

CN119174838APending Publication Date: 2024-12-24ZHONGNAN HOSPITAL OF WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410958270.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing diabetic wound treatment methods cannot effectively target the pathological mechanism of difficult-to-heal the wound, resulting in poor efficacy, and the multifunctional hydrogel has complex chemical structure, long synthesis process, and high cost, making it difficult to achieve large-scale production.

Method used

Develop a sugar-responsive multifunctional hydrogel, which can achieve dynamic crosslinking and enhance mechanical properties by implanting glucose-sensitive benzoic acid monomers in the hydrogel network, Self-healing and adhesion, and is connected to acrylic-co-acrylamide hydrogel by thermal crosslinking to achieve sugar-responsive drug release.

Benefits of technology

The hydrogel releases drugs according to glucose levels in diabetic wounds, has enhanced mechanical properties and adhesion, promotes healing, simplifies the preparation process, is suitable for large-scale production, and provides a new solution for diabetic wound treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174838A_ABST
    Figure CN119174838A_ABST
Patent Text Reader

Abstract

The invention discloses sugar-responsive multifunctional hydrogel as well as a preparation method and application thereof in wound dressing, and belongs to the field of biomedical materials. Functional molecules EGCG-AFPBA with sugar-responsive drug release and dynamic cross-linking effects are prepared, the functional molecules EGCG-AFPBA are connected into an acrylic acid-co-acrylamide hydrogel network in a thermal cross-linking mode, and the synthesized PAE hydrogel has the sugar-responsive drug release function and obtains enhanced mechanical performance, adhesion performance and self-healing performance at the same time. The hydrogel can release drug molecules as required according to the glucose level of the wound surface in the diabetic wound surface, is firmly adhered to the wound surface, isolates infection, creates a wet and mild healing environment, and effectively promotes the healing of the diabetic wound surface. The preparation method is simple, short in process and easy for large-scale production; the obtained hydrogel has sugar-responsive drug release and multiple functions, and a new solution is provided for diabetes wound treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a sugar-responsive multifunctional hydrogel and a preparation method thereof and application thereof in wound dressings. Background Art

[0002] Diabetic wounds are one of the serious complications of diabetes. Their clinical characteristics are prolonged wound healing, excessive exudation, and repeated infections, which often lead to serious consequences such as tissue necrosis and amputation. At present, the clinical treatments for diabetic wounds mainly include surgical debridement and dressing changes, application of antibacterial dressings, negative pressure wound therapy, etc. However, due to the inability to effectively target the specific pathological mechanisms of the difficulty in healing diabetic wounds, the efficacy of these methods often fails to meet expectations. Therefore, more effective treatments are urgently needed to be developed.

[0003] In recent years, with the development of biomaterials, the synthesis and development of new wound dressings has become a research hotspot for the treatment of diabetic wounds. Many biomaterials, including electrospinning, nanofiber membranes, and hydrogels, have been widely studied as functional wound dressings, and have achieved excellent therapeutic effects in in vitro and in vivo experiments. Among them, hydrogels have attracted widespread attention due to their strong functional plasticity and good biocompatibility, and are regarded as ideal materials for the development of a new generation of diabetic wound dressings.

[0004] The pathogenesis of diabetic wounds is complex, with high exudation and severe infection. Ideal dressings need to have drug loading, strong mechanical properties, adhesion, and self-healing properties. However, most of the multifunctional hydrogel dressings currently have complex chemical structures, long synthesis processes, and high costs, which pose many difficulties for practical applications and large-scale production. Summary of the invention

[0005] The purpose of the present invention is to provide a sugar-responsive multifunctional hydrogel and its preparation method and application in diabetic wound dressings in view of the problems existing in the prior art. The present invention implants a phenylboronic acid monomer 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboronic acid (AFPBA) which is highly sensitive to glucose under physiological pH conditions in the hydrogel system, and reversibly combines with the drug molecule epigallocatechin gallate (EGCG) which is rich in hydroxyl groups and has multiple biological activities such as antioxidant and anti-inflammatory properties, so as to achieve "killing two birds with one stone", and at the same time, the sugar-responsive drug release promotes wound healing, and at the same time, the mechanical properties, self-healing properties and adhesion of the hydrogel network are enhanced.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A sugar-responsive multifunctional hydrogel (PAE hydrogel) is an acrylic acid-co-acrylamide (p(AA-Am)) hydrogel containing epigallocatechin gallate (EGCG) and 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboronic acid (AFPBA) cross-linked molecules EGCG-AFPBA. Among them, EGCG-AFPBA is connected to the acrylic acid-co-acrylamide (p(AA-Am)) hydrogel network by thermal cross-linking, and exhibits dynamic binding-dissociation with the change of glucose molecule content in the hydrogel network.

[0008] Wherein, the molar ratio of epigallocatechin gallate to 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboronic acid is preferably 1:1.8-2.2. In the preparation of the acrylic acid-co-acrylamide hydrogel, the ratio of water, acrylic acid, and acrylamide is preferably 10 mL:1.2-1.4 mL:1.6-1.8 g. In the preparation of the sugar-responsive multifunctional hydrogel, the concentration of EGCG-AFPBA added to the acrylic acid-co-acrylamide hydrogel is preferably 7-9 mM.

[0009] The method for preparing the sugar-responsive multifunctional hydrogel comprises the following steps:

[0010] (1) Preparation of EGCG-AFPBA: EGCG and AFPBA are dissolved in a solvent, mixed and allowed to stand to fully crosslink EGCG and AFPBA to obtain an EGCG-AFPBA solution. There are two AFPBA binding sites on each EGCG molecule, so the molar ratio of EGCG to AFPBA is preferably 1:1.8-2.2. The solvent preferably comprises a mixture of any one or more of dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, etc.

[0011] (2) Preparation of sugar-responsive multifunctional hydrogel: Add EGCG-AFPBA solution to premixed AA-Am solution and mix well. The resulting mixture is evacuated in a closed container to remove air, and then vacuum dried to obtain a sugar-responsive multifunctional hydrogel. The premixed AA-Am solution is preferably obtained by a method comprising the following steps: acrylic acid, acrylamide, initiator APS, and catalyst TEMED are added to water and mixed well to obtain an AA-Am solution; wherein the ratio of water, acrylic acid, and acrylamide is preferably 10 mL: 1.2-1.4 mL: 1.6-1.8 g. The concentration of EGCG-AFPBA in the mixture is preferably 7-9 mM. The vacuum drying molding is preferably vacuum dried at 50-70°C.

[0012] The sugar-responsive multifunctional hydrogel is used in wound dressings or in the preparation of wound dressings, and the wound is a diabetic wound.

[0013] Advantages and beneficial effects of the present invention: The present invention utilizes the reaction characteristics of phenylboronic acid molecules and vicinal / meta-diols to form reversible ester bonds, prepares the functional molecule EGCG-AFPBA with both sugar-responsive drug release and dynamic cross-linking, and connects it to the acrylic acid-co-acrylamide (p(AA-Am)) hydrogel network by thermal cross-linking, so that the synthesized PAE hydrogel has the function of sugar-responsive drug release while obtaining enhanced mechanical properties, adhesion properties and self-healing properties. In diabetic wounds, the hydrogel can release drug molecules on demand according to the glucose level of the wound, and at the same time firmly adhere to the wound, isolate infection, and create a moist and gentle healing environment, effectively promoting the healing of diabetic wounds. The preparation method of the present invention is simple, the process is short, and it is easy to mass produce; the obtained hydrogel has both sugar-responsive drug release and multiple functionalities, providing a new solution for the treatment of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 :The morphology and mechanical properties of PAE hydrogels. (A) The morphology and transparency of AA-Am and PAE hydrogels. (B) The deformation properties of PAE hydrogels. (C) The tensile stress-strain curve of PAE hydrogels. (D) The compressive stress-strain curve of PAE hydrogels.

[0015] Figure 2 :Adhesion properties of PAE hydrogel. (A) Adhesion strength of PAE hydrogel on pig skin surface. (B) Comparison of avulsion injury of medical dressing adhesive layer and PAE hydrogel on rat skin. The red arrow marks the subcutaneous bleeding site and the yellow dotted line marks the PAE hydrogel avulsion area. (C) Demonstration of wet adhesion of PAE hydrogel on pig skin surface. (D) Illustration of PAE hydrogel adhesion mechanism.

[0016] Figure 3 :Self-healing properties of PAE hydrogel. (A) Schematic diagram of the self-healing mechanism of PAE hydrogel, including the reconnection of phenylboronic acid ester bonds and hydrogen bonds. (B) The healed PAE hydrogel is subjected to external force. (C) Inflation experiment of the healed PAE hydrogel.

[0017] Figure 4 :Drug release properties of PAE hydrogels. (A) Cumulative release curves of EGCG from different PAE hydrogels. (B) Cumulative release curves of EGCG from PAE8 hydrogels in ordinary PBS and PBS containing high glucose.

[0018] Figure 5 : Cytocompatibility test of PAE hydrogels. (A) Live / dead cell staining after 24 h and (B) 48 h of PAE 8 hydrogel treatment.

[0019] Figure 6: Cell and blood compatibility of PAE hydrogel. (A) L929 cell viability treated with PAE hydrogel extracts of different concentrations. (B) Blood compatibility of PAE hydrogel.

[0020] Figure 7 :The effect of PAE hydrogel on wound healing in diabetic rats. (A) Wound healing effect of rats in different treatment groups. (B) Quantitative treatment of the changes in wound area during the healing process. The experiment was repeated 5 times.

[0021] Figure 8 : Histopathological staining of wound tissue. (A) H&E staining of tissue on day 19 of wound establishment. (B) Masson staining of tissue on day 19 of wound establishment. The red double arrows mark the width of the wound. The blue, yellow, green, and red arrows mark the hair follicles, sebaceous glands, sweat glands, and blood vessels, respectively.

[0022] Fig. 9 : Immunofluorescence staining of wound tissue. On day 19 of wound establishment, wound tissue was stained with (A) CD31 (red fluorescence), (B) macrophage F4 / 80 (green fluorescence) and CD163 (red fluorescence), and (C) TNF-α (green fluorescence). Cell nuclei were stained with DAPI (blue fluorescence). DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0024] Example 1 Preparation of sugar-responsive multifunctional hydrogel (PAE hydrogel)

[0025] 1. Proportion and synthesis of (p(AA-Am)) hydrogel system

[0026] (p(AA-Am)) hydrogel is formed by premixing 99% acrylic acid and 99% acrylamide in pure water, adding initiator APS and catalyst TEMED, and polymerizing in a vacuum drying oven at 60°C. The ratio of AA to Am has a great influence on the performance of the hydrogel after molding. Too much AA will cause the hydrogel to have a low degree of molding and cannot be demolded, while too much Am will cause the hydrogel to be too hard and brittle. Therefore, it is necessary to determine the optimal ratio of AA to Am to optimize the performance of the hydrogel system. Previous results (H.Liu, Y.Wang, Z.Shi, D.Tan, X.Yang, L.Xiong, G.Li, Y.Lei, L.Xue.Fast Self-Assemblyof Photonic Crystal Hydrogel for Wearable Strain and Temperature Sensor[J].Small Methods 2022, 6(7):2200461.) showed that the optimal mass fraction ratio of AA to Am is approximately 1:1 (15wt%). Therefore, the ratio is first adjusted within this range. The specific process is as follows: 10mL of deionized water is added to 6 15mL centrifuge tubes, and 1.2mL AA and 1.8g Am are added to each centrifuge tube; 1.3mL AA and 1.7g Am; 1.4mL AA and 1.6g Am; 1.5mL AA and 1.5g Am; 1.6mL AA and 1.4g Am; 1.7mL AA and 1.3g Am are added to each centrifuge tube respectively. After sufficient stirring and dissolution, add 0.2g APS and 75μL TEMED and mix evenly. After vacuuming for 1min, pour into a closed mold and let stand in a 60℃ vacuum drying oven for 10-15min to form. After demolding, compare the hydrogel formability, stretchability, hardness, and brittleness, and select the optimal ratio for the next experiment. The results showed that when 1.3mL AA and 1.7g Am were added to 10mL deionized water, the obtained AA-Am hydrogel had the best formability and stretchability, and good toughness, so this ratio of AA-Am premix was selected to prepare PAE hydrogel. Note: When there are special requirements for the stretchability, toughness, hardness, etc. of the hydrogel, the above ratio can be adjusted accordingly to obtain a hydrogel that meets the requirements.

[0027] 2. Preparation of EF functional molecules

[0028] Sugar-responsive dynamic cross-linking molecule EF (EGCG-AFPBA) was prepared by dissolving 95% EGCG powder and 95% AFPBA powder in 99% dimethyl sulfoxide solution, mixing by shaking and standing. Considering the molecular structure of EGCG and AFPBA, there are 2 AFPBA binding sites on each EGCG molecule, so the molar ratio should be EGCG: AFPBA = 1: 2 when mixed and dissolved. The specific process of its synthesis is as follows: 46 mg of EGCG and 56 mg of AFPBA were weighed on an analytical balance, added to a centrifuge tube containing 500 μL DMSO, and after being fully mixed on an adjustable mixer, it was left to stand for 10-15 minutes to allow AFPBA and EGCG molecules to fully cross-link, and the target EF solution was obtained.

[0029] 3. Synthesis of Sugar-responsive Multifunctional PAE Hydrogel

[0030] Add EF molecules to the premixed AA-Am solution at a ratio of 3mM (PAE 3), 5mM (PAE 5), and 8mM (PAE 8). For example, add 30μL (3mM), 50μL (5mM), and 80μL (8mM) of EF solution to 2mL of premixed AA-Am solution. Pour the mixed solution into a closed glass container, evacuate the gas, and then place it in a 60℃ vacuum drying oven to form a PAE hydrogel. Note: Too much or too little EF molecules will have an adverse effect on the crosslinking process and the performance of the hydrogel after crosslinking. The ratio of 8mM is the standard after screening in the previous experiment.

[0031] Unless otherwise specified, the PAE hydrogels involved in the tests of the following embodiments refer to PAE 8 hydrogels.

[0032] Example 2 Testing of hydrogel morphology and mechanical properties

[0033] The AA-Am, PAE 3, PAE 5, and PAE 8 hydrogels prepared in Example 1 were placed on papers printed with patterns and words, and photos were taken directly above using a mobile phone to observe their morphology and transparency. At the same time, a PAE 8 hydrogel block was taken and its mechanical properties were preliminarily tested by finger pressure, bending, and twisting. The hydrogel premix was then poured into the tensile and compression sample molds, formed and demolded to prepare for subsequent mechanical property tests. The tensile specimen was dumbbell-shaped, 50 mm long, 4 mm × 2 mm in cross section, and the speed of the universal testing machine was set to 20 mm / min. The compression specimen was cylindrical, with a bottom diameter of 15 mm and a height of 8 mm, and the compression speed was set to 2 mm / min. All mechanical property tests were repeated 5 times.

[0034] like Figure 1-A shows that both AA-Am hydrogel and PAE hydrogel have very good transparency. When applied to the wound, the wound healing can be observed without uncovering it. The mechanical properties of PAE hydrogel were initially tested by finger pressure, twisting and torsion, and it was found that it could withstand and restore its original shape, showing good deformation ability ( Figure 1 -B).

[0035] To further test the mechanical properties of PAE hydrogels, tensile and compressive stress-strain tests were performed using a universal testing machine. As the EF concentration increased, the tensile strength of PAE hydrogels decreased slightly ( Figure 1 -C). The maximum tensile strength of PAE 8 hydrogel is 33.2 kPa. Compared with the AA-Am hydrogel with 380% elongation and 70 kPa tensile strength in the previous study (H. Liu, Y. Wang, Z. Shi, D. Tan, X. Yang, L. Xiong, G. Li, Y. Lei, L. Xue. Fast Self-Assembly of Photonic Crystal Hydrogel for Wearable Strain and Temperature Sensor [J]. Small Methods 2022, 6 (7): 2200461.), PAE hydrogel exhibits a significant yield-softening process, with the tensile strength reduced to about 33 kPa, while the elongation at break of PAE 8 hydrogel increases to about 1000% ( Figure 1 -C), which is about 3 times that of pure AA-Am hydrogel. In the compression test, all three groups of PAE hydrogels can withstand more than 85% compressive strain, while the tensile compressive stress decreases with the increase of EF crosslinker concentration ( Figure 1 -D).

[0036] Example 3 Testing of Hydrogel Adhesion Properties

[0037] A universal testing machine was used to perform shear tensile tests. Two pieces of PAE hydrogel were adhered to both sides of the dry pig skin surface, with a bonding area of ​​15 mm × 15 mm. The outer ends of the two hydrogels were connected to the two ends of the universal testing machine, and the tensile speed was set to 2 mm / min. The adhesion of PAE 3, PAE 5, and PAE 8 hydrogels was tested respectively. At the same time, in the rat skin wound model, PAE hydrogel was compared with ordinary medical dressings (3M TM Tegaderm TM) were attached to the back skin of the depilated rats, and then torn off after firm adhesion. The skin was photographed immediately, and the skin tissue was sent for pathological examination to compare the degree of skin damage after ordinary wound dressing and PAE hydrogel were torn off. Finally, in order to test the adhesion of the hydrogel on the wet skin surface, a piece of fresh pig skin tissue was taken and repeatedly soaked in water to maintain its surface wetness. Then a piece of PAE 8 hydrogel was adhered to its surface, randomly placed in a beaker filled with water and soaked for 3 minutes, then taken out to observe whether the hydrogel was still adhered to the pig skin.

[0038] like Figure 2 As shown in the figure, PAE hydrogel has strong adhesion to pig skin tissue, and due to its flexible material, its peeling damage to the skin is much less than that of ordinary medical dressings. As the EF content in the hydrogel increases, the adhesion of the hydrogel gradually increases. The adhesion strength of PAE 3 hydrogel is 1.5±0.5kPa, while that of PAE 8 hydrogel is 5.6±1.2kPa, and the adhesion has increased by nearly 4 times ( Figure 2 -A). To evaluate the safety of use, we compared the peeling damage of PAE hydrogel and common medical dressing adhesive layer on rat skin tissue. Subcutaneous bleeding was immediately visible after the common medical dressing was peeled off, and epidermal damage was observed in H&E staining ( Figure 2 -B), left. In contrast, no significant changes were observed in the PAE hydrogel group immediately after peeling and in the H&E staining of the skin ( Figure 2 -B, right), indicating its excellent safety in medical wound dressings compared with traditional methods.

[0039] Considering the moist environment caused by excessive exudate in diabetic wounds, the wet adhesion of hydrogel wound dressings is critical. An ideal wound dressing should adhere firmly to the moist wound surface and remove excess exudate from the wound. Therefore, we further evaluated the wet adhesion behavior of PAE hydrogels. PAE 8 hydrogels were applied to moist porcine skin wounds ( Figure 2 -C i-ii ), and then immerse it in water ( Figure 2 -C iii After immersion for 3 minutes and removal from the water, the PAE hydrogel was still firmly attached to the wound site ( Figure 2 -C iv ), showing that it has strong wet adhesion strength and durability underwater. This strong adhesion may be due to the combination of phenolic hydroxyl groups in PAE hydrogels with amino or thiol groups in tissues ( Figure 2 -D).

[0040] Example 4 Testing of Hydrogel Self-Healing Properties

[0041] The self-healing performance of the hydrogel was verified by two experiments. In the first part, a circular hydrogel was cut into two identical parts along the midline, and then the two hydrogel sections were placed in contact in a glass container for 3 minutes. The hydrogel was taken out with tweezers and observed vertically from the bottom to see if it healed. Two tweezers were used to stretch it in opposite directions to test its healing degree. In the second part, a hydrogel that was repeatedly separated and healed was torn apart, then quickly kneaded and combined for 30 seconds to make it oval, and then 10mL of air was quickly injected into the hydrogel using a disposable syringe to see if it broke or broke.

[0042] In addition to its strong adhesion in dry and wet environments, PAE hydrogel (PAE 8) also has excellent self-healing ability. The PAE hydrogel was cut into two parts, and then the two parts were staggered on the cut surface for self-healing ( Figure 3 -B). The results showed that the PAE hydrogel showed obvious self-healing effect after 3 minutes of contact at the damaged interface. The healed hydrogel could not only withstand gravity, but also withstand the tensile force along the healing line ( Figure 3 -B). In addition, after being divided into multiple small pieces and immediately reassembled within 30 seconds, the healed hydrogel could withstand up to 10mL of air expansion ( Figure 3 -C). When the PAE hydrogel is broken by external force, the borate bonds in its structure are broken ( Figure 3 -A, left), however, when the separated surfaces come into contact, these boronates rapidly reorganize through dynamic cross-linking, a process accelerated by the reformation of hydrogen bonds ( Figure 3 -A, right), these factors together lead to the rapid self-healing response of PAE hydrogel.

[0043] Example 5 Testing of the Responsive Drug Release Performance of Hydrogel Sugar

[0044] The release of EGCG in PAE hydrogel was evaluated in PBS buffer. First, 1 g of PAE 3, PAE 5 and PAE 8 hydrogels were added to centrifuge tubes containing 20 mL of PBS solution (pH 7.4), respectively. The mixture was incubated at 37 ° C with shaking for different times. At each time point, 3 mL of supernatant was extracted and 3 mL of PBS solution was added for volume compensation. The concentration of released EGCG was determined by measuring the absorbance of the extracted supernatant at 276 nm using a UV-visible spectrophotometer. The cumulative release of EGCG in the hydrogel was expressed as a percentage of the released drug and plotted against the incubation time. On this basis, the glucose-responsive release properties of PAE hydrogels were further evaluated. 1 g of PAE 8 hydrogel was placed in PBS or PBS containing 25 mM glucose and incubated at 37 ° C, and the cumulative release of EGCG was measured at different time points. Similarly, the drug release curve was measured according to the glucose concentration and plotted as described above.

[0045] As the PAE hydrogel swells, its internal structure gradually decomposes and releases the drug molecule EGCG. First, the drug release properties of the PAE hydrogel were evaluated in PBS ( Figure 4 -A). PAE 3 hydrogel released about 90% of EGCG in the first 3 days and completed the release within 6 days, while PAE 5 and PAE 8 hydrogels showed slower release rates and reached the maximum release on the 14th and 16th days, respectively ( Figure 4 -A). A lower concentration of EF molecules (PAE 3) resulted in a faster release rate, which may be due to the lower cross-linking density of the hydrogel network. It should be noted that EGCG release from PAE hydrogels can lead to a weakening of their tissue adhesion, a process that facilitates the removal of PAE hydrogel dressings after use.

[0046] Due to the dynamic bonding between EGCG and AFPBA, PAE hydrogels are responsive to polyols such as glucose. To investigate the glucose-responsive release properties of PAE hydrogels, we studied the drug release profiles of PAE 8 hydrogels in PBS containing different glucose concentrations. In contrast, the EGCG release rate of PAE hydrogels in high glucose solution (HG) was much faster than that in PBS ( Figure 4 -B).

[0047] Example 6 Testing of Hydrogel Biocompatibility

[0048] 1. Cell Recovery

[0049] First, turn on the water bath and set the temperature to 37°C for preheating. Next, remove the required L929 cells from the liquid nitrogen tank and take necessary safety measures to avoid frostbite caused by liquid nitrogen, wearing safety glasses, thick gloves and protective clothing. Use a long pair of tweezers to hold the cryotube tightly and carefully immerse it in the preheated water to thaw. During the thawing process, continue to stir and pay attention to ensure that the cryosol is completely thawed within two minutes. Then put the cryotube into the centrifuge, set the speed to 1000 rpm, and centrifuge for 5 minutes. After that, disinfect the outside of the cryotube with alcohol and move it into the biosafety cabinet. Pour off the supernatant and use a pipette to accurately draw 1mL of fresh serum-containing medium to resuspend the cells. Next, transfer the resuspended cells to a cell culture flask, add 3mL of fresh serum-containing medium, and gently shake to mix. Finally, place the culture flask containing the cells in a centrifuge set at 37°C and 5% CO 2 Incubator for further cell culture.

[0050] 2. Cell culture medium replacement and cell subculturing

[0051] When culturing cells, check the color of the culture medium by visual observation. If the culture medium tends to be yellow, it indicates that the pH may be reduced and the culture medium should be replaced in time. At the same time, check the cell confluence under a microscope. When it reaches 70% to 90%, it also indicates that the medium needs to be replaced or the cells need to be passaged.

[0052] When changing the medium, first completely aspirate the old medium. Next, use a pipette to add 2 mL of PBS for rinsing, shake the culture flask a few times to ensure that the impurities on the cell surface are cleaned, then aspirate the PBS and replace it with fresh serum-containing medium, then put the culture flask back into the set incubator (37°C, 5% CO 2 )Continue to cultivate.

[0053] When cell passaging is required, similar procedures for changing the medium should be followed. After washing the cells that have grown on the wall with PBS, add 1 mL of trypsin solution, shake gently, and place the culture flask back in the incubator for about 2 minutes for digestion. During this period, the cells should begin to fall off from the bottom of the culture flask. Then confirm under a microscope whether the cells have fallen off. If so, add 2 mL of serum-containing culture medium, gently blow and wash the cells, collect the cell suspension and transfer it to a centrifuge tube. Centrifuge at 1000 rpm for 5 minutes, remove the supernatant, resuspend the cells with 1 mL of serum-containing culture medium, and distribute them to new culture flasks at a ratio of 1:2 to 1:5, add 3 mL of fresh serum-containing culture medium and shake gently, and finally place in an incubator (37°C, 5% CO 2 )Continue to culture cells.

[0054] 3. Cell plating and co-culture

[0055] 100 mg of PAE hydrogel was taken and cultured in 10 mL of serum-containing culture medium for 24 h (37°C) to fully release the drug. Then, the PAE hydrogel conditioned medium (10 mg / mL) was obtained by filtering with a 0.22 μm filter, and then the conditioned medium was diluted in a gradient manner to obtain conditioned medium of different concentrations.

[0056] In order to verify the cell compatibility of PAE hydrogel, live / dead cell staining experiment was performed on L929 cells. First, L929 cells were plated at 8×10 4 The cells were planted into 6-well plates at a density of 100 μg / well and cultured in serum-containing medium for 12 h. After the cells adhered to the wall, PAE hydrogel conditioned medium (10 mg / mL) was added, and cells cultured in conventional serum-containing medium were used as the control group. After 24 h or 48 h of continuous culture, 1 mL of calcein-AM / PI dye was used for staining for 30 min to mark live cells (green fluorescence) and dead cells (red fluorescence), respectively. Then, an inverted fluorescence microscope was used to observe the cell survival / death status. All the above experiments were repeated at least three times.

[0057] To further verify the biocompatibility of the hydrogel, the L929 cells in good condition were eluted according to the above method, seeded into a 96-well plate at a density of 2000 cells / well, and then returned to the constant temperature incubator for 12 hours to grow attached to the wall. After complete attachment under the microscope, the original culture medium was aspirated, and 100 μL of PAE hydrogel conditioned medium with different concentrations (1, 2.5, 5, 7.5, 10 mg / mL) was added to the experimental group wells, and the conventional serum-containing culture medium was used as the control group. After 37°C, 5% CO 2 After culturing for 24 h and 48 h, the 96-well plate was taken out and 10 μL of CCK-8 solution was added to each well. After reacting for 2 h, the absorbance value of each group of wells was read at 450 nm using a multifunctional microplate reader. The cell activity value was calculated using the following formula: Cell activity = A t / A c *100%, of which A t With A c Represent the absorbance values ​​of the experimental group and the control group, respectively.

[0058] In the hydrogel cell compatibility test, live / dead cell staining showed that there was no significant difference in the proliferation trend and cell morphology of L929 cells in the control group and the PAE hydrogel (PAE 8) treatment group during the growth period of 24h to 48h ( Figure 5 -A, Figure 5 -B), preliminarily showing the good biocompatibility of PAE hydrogel.

[0059] The CCK-8 method was further used to test the cell viability of cells treated with different concentrations of PAE hydrogel (PAE 8) extracts at 24h and 48h. It was found that even when the hydrogel concentration reached the highest 10mg / mL, the cell viability was still greater than 95%, and there was no significant difference with the control group ( Figure 6 -A).

[0060] In terms of blood compatibility testing, 100 mg of PAE (3, 5, 8) hydrogel was first taken, incubated at 37°C in 10 mL of PBS (pH 7.4), and shaken at 100 rpm for 24 hours. The supernatant was collected and filtered using a 0.22 μm filter to obtain a PAE hydrogel extract. Fresh rat blood was collected and centrifuged at 1500 rpm for 30 minutes to completely remove the serum. The harvested red blood cells (RBCs) were diluted to 16% (v / v) with PBS. The diluted RBCs were then incubated with the hydrogel extract at 1:1 (v / v) at 37°C for 1 hour. PBS solution and Triton X-100 (1%) treated RBCs were used as negative control group and positive control group, respectively. Afterwards, the suspension was collected and centrifuged at 1500 rpm for 10 minutes. The supernatant was collected and the absorbance was measured at 541 nm using a multifunctional microplate reader. The hemolysis rate was calculated as follows: Hemolysis rate = (A t -A n / A p -A n )*100%. Among them, A t , A n and A p The absorbances of the hydrogel extract group, negative control group, and positive control group are shown in Figure 2. Compared with the positive control group, no significant hemolysis was found in the blood treated with PAE 3, PAE 5, and PAE 8 hydrogels, and the degree of hemolysis was no different from that of the negative control group ( Figure 6 -B). These results verified the good biocompatibility of PAE hydrogel.

[0061] Example 7 Testing of the ability of hydrogel to promote diabetic wound healing

[0062] 1. Methods

[0063] 1. Induction of Diabetic Rats

[0064] 20 SD rats were allocated 2 per cage and adapted to the environment for 2-3 days in advance. 1% streptozotocin was prepared and injected intraperitoneally at 50 mg / kg once a day for 3-5 days. Then blood was collected by tail blood collection needle every 3 days and blood glucose level was monitored by blood glucose meter. The model was considered successful when the blood glucose level was greater than 16.7 mmol / L for 2 consecutive weeks.

[0065] 2. Construction of wound model

[0066] The rats were fasted for 12 hours in advance, and their blood sugar levels were measured before the experiment to see if they met the standard. Rats were anesthetized by inhalation of sevoflurane until the rats had low muscle tone and no corneal reflex. The skin on the back of the rats was shaved and disinfected, and a 1.2 cm diameter round hole was selected for the tissue biopsy puncture. The assistant lifted the skin on the back of the rat with both hands, and the surgeon punched holes twice at the same height on the back of the rat to form four wounds symmetrical along the long axis of the rat's body. Dressings or drugs were applied to the wounds on the back of the rats according to the grouping, and transparent dressings were used to fix them when necessary. After the operation, the rats were returned to the cage and marked with groups. Cotton pads were used to keep warm, and the vital signs of the rats were closely monitored until they woke up. After the operation, cotton pads were used to keep warm and resume normal diet.

[0067] 3. Experimental Animal Grouping

[0068] (1) Negative control group, the wound surface was not treated;

[0069] (1) AA-Am hydrogel-treated group;

[0070] (2) EF solution spraying treatment group;

[0071] (4) PAE hydrogel (PAE 8) treatment group;

[0072] (5) Positive control group, using Convatec's diabetic wound hydrocolloid dressing

[0073] 4. Animal treatment time and specimen processing

[0074] After the wound model was completed, the wound was observed every 3 days, and the dressing was removed to take photos of the wound. The dressing was changed every 7 days. On day 19 after the wound was established, the rats in different groups were killed by intraperitoneal injection of an overdose of pentobarbital. The wound tissue was obtained and fixed with paraformaldehyde for subsequent tissue pathological staining.

[0075] 5. Gross observation and evaluation of wound surface

[0076] The wound surface was observed every 3 days, the wound healing status of each group was compared, and the wound surface was photographed after the dressing was removed. When taking pictures, the camera was kept directly above the wound surface and a ruler was placed on it.

[0077] 6. Histopathological Evaluation

[0078] The wound tissues were taken for H&E staining and Masson staining. The specific process is as follows:

[0079] (1) Before starting the experiment, ensure that all necessary instruments, consumables, and reagents are ready. Then, take out the prepared paraffin-embedded tissue sections and treat them sequentially with xylene and alcohol to remove the paraffin until they can be rinsed with water.

[0080] (2) Add hematoxylin staining solution to the sections for staining for 2-3 minutes, then rinse thoroughly with distilled water to remove the remaining staining solution. Next, add differentiation solution to the sections for 7 seconds, and then soak the sections in a staining rack in tap water for 15 minutes.

[0081] (3) After soaking, remove the slices and remove excess water with absorbent paper. Then, add eosin staining solution to stain the slices for 6-7 minutes, wash again with distilled water to remove excess staining solution, and then put the slices back on the staining rack.

[0082] (4) The sections are then dehydrated and transparentized by sequentially placing them in xylene and ethanol.

[0083] (5) Apply a small drop of neutral gum on the slice to fix the slice, and finally cover it with a coverslip to complete the sealing.

[0084] (6) After sealing, take photos of the sections under a microscope.

[0085] 7. Immunofluorescence Assay

[0086] The wound tissues were taken for immunofluorescence staining. The specific process was as follows:

[0087] (1) Before starting the experiment, ensure that all necessary experimental tools, consumables, and reagents are ready. Take out the previously prepared paraffin-embedded tissue sections and dewax them using xylene and alcohol in sequence until the sections can be rinsed with water.

[0088] (2) Immerse the tissue sections in citric acid antigen retrieval solution and place them in a microwave-assisted antigen retrieval device for heating and retrieval.

[0089] (3) After repair, remove the slices and allow them to cool naturally to room temperature. Next, wash the slices three times with PBS buffer, 5 minutes each time. After washing, gently shake the slices dry, use a marker to draw a boundary around the slices and mark them, slowly drip the antigen blocking solution into the marked area, and then place the slices in a wet box and incubate at room temperature for 1 hour.

[0090] (4) After incubation, gently shake off excess blocking solution and add the pre-prepared primary antibody solution. Place the sections back into the humidified chamber and incubate at 4°C for at least 16 hours.

[0091] (5) Remove the slices and wash them three times with PBS buffer for 5 minutes each time to remove the residual primary antibody and avoid affecting the subsequent experiments. After washing, gently shake dry and then add the pre-prepared secondary antibody working solution. Then, transfer the slices back to the humidified box and incubate them in a dark environment at 37°C for 1 hour.

[0092] (6) After incubation, wash the sections again with PBS buffer for 3 times, 10 minutes each time, to remove the remaining antibodies. Then shake the sections dry, add mounting solution, mount the sections, and observe and photograph them under a fluorescence microscope.

[0093] 2. Results

[0094] 1. Wound healing speed

[0095] In all treatment groups, PAE and AA-Am hydrogels had high transparency, and the wound surface could be directly observed. The transparency of the dressing is poor, and the wound surface cannot be clearly observed ( Figure 7 -A). In terms of wound recovery, the wound healing speed of the PAE hydrogel group was significantly faster than that of the negative control group, EF and AA-Am groups ( Figure 7 -A), which was also confirmed by wound area change analysis ( Figure 7 -B). On the 6th day after wound establishment, the wound area of ​​the negative control group was 69.4% of the initial area, while that of the PAE hydrogel group was 28.9%. On the 13th and 19th days, the average wound area of ​​the negative control group was 25.3% and 21.0% of the initial area, respectively. In contrast, in the PAE hydrogel group, this area was 14.8% and 10.4%, respectively ( Figure 7 -B). It is worth noting that from the 13th day to the 19th day, the wound healing rate of all groups decreased significantly, which reflects the chronic healing characteristics of diabetic wounds. The dressing, a hydrocolloid dressing specially used for treating diabetic wounds and chronic wounds, was considered as a positive control. The wound healing speed of the two groups was similar, and there was no significant difference in wound area at each time point ( Figure 7 -B), verifying the efficient wound healing performance of PAE hydrogel.

[0096] 2. H&E and Masson staining of wound tissue

[0097] H&E staining showed that on the 19th day after wound establishment, all wounds showed complete epithelialization ( Figure 8 -A), and angiogenesis and regeneration of skin appendages such as hair follicles, sweat glands, and sebaceous glands occurred. However, the wound width of the PAE hydrogel group was the smallest, indicating that the wounds treated with PAE hydrogel healed faster.

[0098] Masson staining is usually used to detect collagen deposition and vascularization in tissues. In general, the AA-Am group and the PAE group had higher collagen deposition density, and the PAE group showed the best vascularization level, with more new blood vessels in the wound tissue and a large blood vessel passing through the center of the wound ( Figure 8 -B).

[0099] 3. Immunofluorescence staining of wound tissue

[0100] First, we evaluated the vascularization level of wound tissue by CD31 staining. Compared with the control group, the PAE hydrogel group showed stronger fluorescence intensity and larger positive area, while the CD31 positive area of ​​other groups did not differ significantly from that of the control group ( Fig. 9 -A). It shows that PAE hydrogel has a good effect in promoting angiogenesis.

[0101] The polarization state of macrophages is an important indicator for judging the level of inflammatory response. When macrophages mainly show the pro-inflammatory M1 type, they will release more inflammatory cytokines, leading to tissue destruction and organ dysfunction. In contrast, when the number of anti-inflammatory M2 macrophages increases, more anti-inflammatory cytokines and growth factors are released, thereby enhancing tissue repair and regeneration. In the immunofluorescence staining of F4 / 80 and CD163, the macrophages in the control group mainly showed the M1 type (F4 / 80+, CD163-), and similar situations were found in the EF and AA-Am groups ( Fig. 9 -B). In the PAE hydrogel-treated group, the fluorescence signals of both M1 and M2 macrophages were weak. In contrast, in the PAE hydrogel-treated group, the proportion of M2 macrophage phenotype increased significantly (F4 / 80+, CD163+), verifying the regulatory effect of PAE hydrogel on macrophage phenotype.

[0102] To detect the overall level of inflammation in the wound tissue, we performed TNF-α immunofluorescence staining. The results showed that the inflammation levels in the control group, EF group, and AA-Am group were very high, and the TNF-α signal was strong and wide ( Fig. 9 -C). The inflammation level in the group was slightly weaker, but the inflammation levels in the above groups were much higher than that in the PAE hydrogel treatment group. The results showed that PAE hydrogel can effectively reduce the inflammatory response in the wound and promote wound healing.

[0103] The above embodiments are only used to help illustrate the present invention. The implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A sugar-responsive multifunctional hydrogel, characterized in that: The sugar-responsive multifunctional hydrogel is an acrylic acid-co-acrylamide hydrogel containing epigallocatechin gallate and 4-(2-acrylamideethylcarbamoyl)-3-fluorophenylboronic acid cross-linking molecules.

2. The sugar-responsive multifunctional hydrogel according to claim 1, characterized in that: Epigallocatechin gallate and 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboronic acid cross-linking molecules were connected to the acrylic acid-co-acrylamide hydrogel network by thermal cross-linking.

3. The sugar-responsive multifunctional hydrogel according to claim 1, characterized in that: The molar ratio of epigallocatechin gallate to 4-(2-acrylamideethylcarbamoyl)-3-fluorophenylboric acid is 1:1.8-2.

2.

4. The sugar-responsive multifunctional hydrogel according to claim 1, characterized in that: In the preparation of the acrylic acid-co-acrylamide hydrogel, the ratio of water, acrylic acid and acrylamide is 10 mL: 1.2-1.4 mL: 1.6-1.8 g.

5. The sugar-responsive multifunctional hydrogel according to claim 1, characterized in that: In the preparation of the sugar-responsive multifunctional hydrogel, epigallocatechin gallate and 4-(2-acrylamideethylcarbamoyl)-3-fluorophenylboronic acid cross-linking molecules are added to the acrylic acid-co-acrylamide hydrogel at a concentration of 7-9 mM.

6. The method for preparing the sugar-responsive multifunctional hydrogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dissolving epigallocatechin gallate and 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboric acid in a solvent to fully cross-link the two; (2) adding the cross-linked molecules obtained in step (1) to the acrylic acid-co-acrylamide solution and mixing evenly, evacuating the air, and vacuum drying to obtain a sugar-responsive multifunctional hydrogel.

7. The preparation method according to claim 6, characterized in that: In step (1), the solvent comprises a mixture of any one or more of dimethyl sulfoxide, N-methylpyrrolidone, and dimethylformamide.

8. The preparation method according to claim 6, characterized in that: In step (2), the acrylic acid-co-acrylamide solution is obtained by a method comprising the following steps: adding acrylic acid, acrylamide, an initiator, and a catalyst into water and mixing them evenly to obtain an acrylic acid-co-acrylamide solution; and the vacuum drying and molding is vacuum drying and molding at 50-70°C.

9. Use of the sugar-responsive multifunctional hydrogel according to any one of claims 1 to 5 in wound dressings or in the preparation of wound dressings.

10. The use according to claim 9, characterized in that: The wound surface is a diabetic wound surface.